The Book of Lost Hours - Gelfuso, Hayley (New York : Atria Books, 2025)
"A spectacular historical and speculative novel about a WWII-era girl who grows up trapped in the "time space," a cavernous library featuring books that house memories--but while government agents burn memories they wish to erase, she saves them, until an affair with an American CIA agent as a young woman changes the course of her life"--.
new book 2025 fall.
Keywords: Clock and watch makers; Libraries; Memory; Historical fiction; Space and time; Time travel; Time travel -- Fiction; Science fiction; Time-travel fiction; Novels